CULTURE STUDIES DALAM NOVEL TARIAN BUMI KARYA OKA RUSMINI - Florensia Carliani Mbues; Eko Cahyo Prawoto (Universitas PGRI Adi Buana Surabaya, 2020)
This study aims to examine the existing culture in the novel Tarian Bumi. In conducting this research the researcher used a qualitative descriptive method. Qualitative method means that the resulting data the form of words in the form of quotations. The main data source in this study came from Oka Rusmini's Novel Cultural Studies in the Earth Dance Novel. The data obtained in this study used reading techniques, note-taking techniques and literature study techniques with steps to read carefully, directed, thoroughly and understand after that were analyzed. In this cultural study, there are 3 values ​​contained, which are the focus of research on the novel Tarian Bumi, the first is the value of belief. This belief value exists and is highly depicted in the novel Tarian Bumi. The value of belief in the novel Tarian Bumi is described in three relationships, namely Intrapersonal (the relationship between oneself), Interpersonal (the relationship between other people and the environment) and Transpersonal (a relationship that cannot be seen from a relationship with divinity which is the highest power). Second, Moral values. The moral values ​​described in the novel Tarian Bumi can seen the actions or behavior of characters in the Tarian Bumi novel. The three values ​​of Customs. The values ​​of these customs are seen to be very attached to the traditional Balinese Hindu rituals and all kinds of rules that exist in the Brahmana and Sudra aristocrats.